2016
DOI: 10.1051/0004-6361/201629103
|View full text |Cite
|
Sign up to set email alerts
|

The seven sisters DANCe

Abstract: Context. Stellar clusters are open windows to understand stellar evolution. Specifically, the change with time and the dependence on mass of different stellar properties. As such, they are our laboratories where different theories can be tested. Aims. We try to understand the origin of the connection between lithium depletion in F, G and K stars, rotation and activity, in particular in the Pleiades open cluster. Methods. We have collected all the relevant data in the literature, including information regarding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 95 publications
0
26
0
Order By: Relevance
“…This quantity involves a geometric projection factor which limits its applicability, in particular for low v sin i which may correspond to truly slow rotators or moderate/fast rotators seen at a low inclination. Prior to the recent studies of Gondoin (2014), Barrado et al (2016), and Somers & Stassun (2017), only King et al (2000) had previously used preliminary estimates of rotational periods derived from the photometric modulation of the stellar luminosity by surface spots. Even though these were much fewer and not nearly as accurate as the Kepler K2 periods used here, King et al (2000) claimed that a few Pleiades K dwarfs with long rotational periods, that is, true slow rotators, were exhibiting Li-excess.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This quantity involves a geometric projection factor which limits its applicability, in particular for low v sin i which may correspond to truly slow rotators or moderate/fast rotators seen at a low inclination. Prior to the recent studies of Gondoin (2014), Barrado et al (2016), and Somers & Stassun (2017), only King et al (2000) had previously used preliminary estimates of rotational periods derived from the photometric modulation of the stellar luminosity by surface spots. Even though these were much fewer and not nearly as accurate as the Kepler K2 periods used here, King et al (2000) claimed that a few Pleiades K dwarfs with long rotational periods, that is, true slow rotators, were exhibiting Li-excess.…”
Section: Discussionmentioning
confidence: 99%
“…31881corr that among cluster members less massive than about 0.9M , those with the highest projected rotational velocities were systematically lithium-rich compared to their similar-mass, lowvelocity siblings. Subsequent studies confirmed these early results and showed that the lithium spread affects mostly earlyto mid-K stars in the Pleiades cluster (e.g., Russell 1996;King et al 2000; Barrado et al 2016), while late-K and M dwarfs are heavily lithium depleted (e.g., Garcia Lopez et al 1994;Oppenheimer et al 1997) down to near the hydrogen burning mass limit where lithium starts to reappear Rebolo et al 1996;Stauffer et al 1998). Since then, additional examples of a lithium-rotation connection among low-mass dwarfs have been reported for young open clusters (e.g., M34 andNGC 2516, Jones et al 1997;Jeffries et al 1998, respectively), young moving groups (e.g., β Pic, Messina et al 2016), and even for star forming regions as young as 5 Myr (e.g., NGC 2264.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, the chromospheric activity can also be corre-lated with rotation (Bouvier 1990), thus, fast rotators may have inflated radii. In fact, fast rotators during the early pre-MS phase may have their radii enlarged by strong magnetic fields (Somers & Pinsonneault 2014;Barrado et al 2016, and references therein).…”
Section: The Mass-radius Diagram and The Radius Anomaly Problemmentioning
confidence: 99%